Semiartificial Magnetotactic Bacteria: Nanoparticle‐Regulated Semiartificial Magnetotactic Bacteria with Tunable Magnetic Moment and Magnetic Sensitivity (Small 15/2019). Issue 15 (12th April 2019) - Li, Qilong; Chen, Haitao; Feng, Xueyan; Yu, Chanchan; Feng, Feng; Chai, Yahong; Lu, Pan; Song, Tao; Wang, Xiuyu; Yao, Li
Abstract : In article number1900427, Xiuyu Wang, Li Yao, and co‐workers produce semi‐artificial magnetotactic bacteria (SAMTB) with synthetic magnetic nanoparticles on the surface of MTB. The SAMTB retain the advantages of strong mobility and magnetotaxis of natural MTB while realizing tunable magnetic properties and magnetotactic motion.